BREAKING BARRIERS: EXPLORING THE IMPACT OF THE GLASS CEILING ON PAKISTANI UNIVERSITIES - Shabana Khurshid; Fakhra Aziz (International Journal of Contemporary Issues in Social Sciences, 2024)
The glass ceiling is the concept related to barriers to upward mobility in the workplace, particularly for women and underrepresented groups. Glass ceilings refer to the invisible barriers preventing people from reaching higher positions despite their qualifications and experience. The primary objective of this research project was to recognize Gender Discrimination via Glass Ceiling effects, which involve vertical discrimination in terms of promotions and pay disparities. The researcher employed the positivist research paradigm. Under the typology of positivism descriptive method approach was used. The data were collected through a questionnaire. By examining the impact of glass ceilings, the study potentially identified areas where universities can improve their practices and policies to promote diversity and inclusion, to determine which method leads to better performance and outcomes for all students. The comparative aspect of the study (i.e., comparing private and public universities) also provided insight into how different types of institutions approach diversity and inclusion and how they impact student outcomes. Such findings could be used to inform policy decisions and provide guidance for universities looking to improve their diversity and inclusion efforts. Overall, the study has the potential to make an important contribution to the field of higher education, particularly in Pakistan, by highlighting the influence of glass ceilings on university performance and identifying potential strategies to address these issues.